2016
DOI: 10.1371/journal.pcbi.1005141
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Properties of Dimensionality Reduction for Neural Populations and Network Models

Abstract: Recent studies have applied dimensionality reduction methods to understand how the multi-dimensional structure of neural population activity gives rise to brain function. It is unclear, however, how the results obtained from dimensionality reduction generalize to recordings with larger numbers of neurons and trials or how these results relate to the underlying network structure. We address these questions by applying factor analysis to recordings in the visual cortex of non-human primates and to spiking networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
152
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(162 citation statements)
references
References 60 publications
8
152
2
Order By: Relevance
“…corresponding to the first five modes calculated using factor analysis (33,68). B) Changes in average covariance associated with contrast, adaptation and attention in V4 or task switching in V1 between each unit's raw (left) or residual (first eigenmode removed) responses and all other simultaneously recorded units.…”
Section: Figure 4 -Contrast Adaptation and Attention Affect Populatimentioning
confidence: 99%
See 1 more Smart Citation
“…corresponding to the first five modes calculated using factor analysis (33,68). B) Changes in average covariance associated with contrast, adaptation and attention in V4 or task switching in V1 between each unit's raw (left) or residual (first eigenmode removed) responses and all other simultaneously recorded units.…”
Section: Figure 4 -Contrast Adaptation and Attention Affect Populatimentioning
confidence: 99%
“…We showed recently that measuring how trial-to-trial response variability is shared across a neuronal population and how that covariability depends on sensory or cognitive processes provides strong constraints on a model of visual cortex. We and others have shown that covariability of firing rates in visual cortex is typically low rank (2)(3)(4)(29)(30)(31)(32)(33)(34)(35). This means that shared variability is well-described as a low-dimensional process that affects neurons with different weights rather than higher order interactions between neurons or subpopulations.…”
mentioning
confidence: 95%
“…Even though information is highly distributed across neurons in a population, most variability is captured by a low-dimensional subspace, leading to suggestions that we might only need to consider the information encoded in this subspace (Williamson et al, 2016). As we have shown, this argument does not consider that information does not only depend on variability, but also on how the signal aligns with this variability (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Previous work has observed that most neural population activity fluctuations are constrained to a low-dimensional linear subspace that is embedded in the high-dimensional space of neural activity (Engel & Steinmetz, 2019;Semedo, Zandvakili, Machens, Yu, & Kohn, 2019;Williamson et al, 2016). This might suggest that focusing on such a low-dimensional subspace is sufficient to understand brain function (Williamson et al, 2016).…”
Section: Information Is Not Well-aligned With Principal Noise Dimensionsmentioning
confidence: 99%
“…The dynamics of single neurons within a given brain circuit are not independent, but highly correlated. Moreover, neural activity is often dominated by only a very low number of distinct correlation patterns [Churchland et al, 2012, Mante et al, 2013, Kaufman et al, 2014, Cunningham and Yu, 2014, Gao and Ganguli, 2015, Williamson et al, 2016, Pang et al, 2016, Mazzucato et al, 2016, Michaels et al, 2016, Elsayed and Cunningham, 2017, Gallego et al, 2017, Williams et al, 2018, Rus, 2018, Semedo et al, 2019. This implies that there exists a low-dimensional manifold in the high-dimensional population activity space, which most of the variance of the neural activity is confined to.…”
Section: Introductionmentioning
confidence: 99%